Pros and cons of digital access to healthcare services and healthcare utilization: a quasi-experiment - Antinyan, Armenak; Bellio, Stefania; Bertoni, Marco; Corazzini, Luca; Longone, Michela; Narne, Elena (Frontiers in Behavioral Economics, 2024)
Objectives. We study the introduction of a web portal allowing women to manage their appointments in the public cervical cancer screening program of an Italian Local Health Unit (LHU). We investigate how this intervention affects program participation and the ability of the LHU to collect information on women's screening outside the program.Methods. We use administrative data from the LHU and a difference-in-differences design to compare outcomes of women in the treated group (n=870), who could reschedule appointments either through phone calls or through the portal, and the control group (n=768), who could only reschedule by phone.Results. The portal reduces the number of appointments rescheduled by phone (b= -0.176, 95% CI = -0.228 –0.114, p<0.001). It also makes women more likely to report both screenings outside the program (b=0.049, 95% CI = 0.006 -0.912, p<0.05) and the various reasons for cancelling their appointments. However, the portal also decreases the probability of screening (b=-0.156, 95% CI = -0.216 -0.096, p<0.001). Two-thirds of this reduction is due to increased unjustified no-shows (b= 0.099, 95% CI = 0.043 -0.155, p<0.001).Digital innovations increase efficiency of screening programs. However, they may discourage screening, by triggering behavioural biases such as limited attention and procrastination.Pairing portals with frequent reminders may help to boost participation.